2020
DOI: 10.1186/s13195-020-00723-1
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in people with predementia Alzheimer’s disease, mild cognitive impairment or dementia measured with preference-based instruments: a systematic literature review

Abstract: Background Obtaining reliable estimates of the health-related quality of life (HR-QoL) of people with predementia Alzheimer’s disease [AD] (preclinical or prodromal AD), mild cognitive impairment (MCI) and dementia is essential for economic evaluations of related health interventions. Aims To provide an overview of which quality of life instruments are being used to assess HR-QoL in people with predementia AD, MCI or dementia; and, to summarise their reported HR-QoL levels at each stage of the disease and by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 29 publications
0
62
0
Order By: Relevance
“…Patient utilities for individuals with MCI due to AD and AD dementia were selected from a systematic literature review and meta-analysis by Landeiro et al [ 45 ], which included self-reported and proxy-reported utilities for individuals at each AD severity health state (Table S3 in the electronic supplementary material). In the model, the proxy-reported European Quality of Life-5 Dimensions (EQ-5D) estimates were used because patients in later stages of AD dementia may provide less reliable self-rated assessments [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…Patient utilities for individuals with MCI due to AD and AD dementia were selected from a systematic literature review and meta-analysis by Landeiro et al [ 45 ], which included self-reported and proxy-reported utilities for individuals at each AD severity health state (Table S3 in the electronic supplementary material). In the model, the proxy-reported European Quality of Life-5 Dimensions (EQ-5D) estimates were used because patients in later stages of AD dementia may provide less reliable self-rated assessments [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…In line with previous systematic reviews in AD [ 32 , 33 ], the quality assessment of the reviewed clinical studies was performed using the Effective Public Health Practice Project (EPHPP) Quality Assessment Tool, and classified according to their global rating as having low (no “Weak” ratings), moderate (one “Weak” rating) or high (two or more “Weak” ratings) risk of bias [ 34 ]. For animal studies, the Stroke Therapy Academic Industry Roundtable (STAIR) preclinical recommendations were used [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is a general scale, which does not distinguish between MCI patients and participants with normal cognitive function. It is short, easy to use and has good feasibility, acceptability and reliability [ 24 ]. In a cross-sectional study of an urban general population in China [ 25 ], it showed moderate level of test–retest reliability.…”
Section: Methodsmentioning
confidence: 99%